Mikroposesor intel : 8086/8088, 80186/80188/8086, 80386, 80486, Pentium, Pentium Pro, dan Pentium II: arsitektur, pemograman an, antarmuka - Hanum, Yuhilza (Erlangga, 2003)
Judul asli: The Intel microprocessor. JIlid 2